2006
DOI: 10.1016/j.cbpa.2006.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Environmental rearing conditions produce forebrain differences in wild Chinook salmon Oncorhynchus tshawytscha

Abstract: Recent studies suggest that hatchery-reared fish can have smaller brain-to-body size ratios than wild fish. It is unclear, however, whether these differences are due to artificial selection or instead reflect differences in rearing environment during development. Here we explore how rearing conditions influence the development of two forebrain structures, the olfactory bulb and the telencephalon, in juvenile Chinook salmon (Oncorhynchus tshawytscha) spawned from wild-caught adults. First, we compared the sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 46 publications
3
72
0
4
Order By: Relevance
“…Working with brown trout ( Salmo trutta ), Kolm and colleagues [89] found that sneaker males had larger brains relative to their body size than migratory bourgeois males, although the cerebellum was relatively larger in the migratory morph. This brain difference is consistent with other studies demonstrating plasticity in salmonid brains [79,101]. As with the GnRH differences described between male phenotypes in bluehead wrasses in section 2, the HPG axis is important in differentiating parr from immature migratory males in Atlantic salmon with the maturing parr showing greater LHÎČ and FSHÎČ subunit mRNA levels in the pituitary, greater LH and FSH receptor mRNA in the testes, and greater testis size and 11KT levels.…”
Section: Alternative Male Phenotypessupporting
confidence: 91%
“…Working with brown trout ( Salmo trutta ), Kolm and colleagues [89] found that sneaker males had larger brains relative to their body size than migratory bourgeois males, although the cerebellum was relatively larger in the migratory morph. This brain difference is consistent with other studies demonstrating plasticity in salmonid brains [79,101]. As with the GnRH differences described between male phenotypes in bluehead wrasses in section 2, the HPG axis is important in differentiating parr from immature migratory males in Atlantic salmon with the maturing parr showing greater LHÎČ and FSHÎČ subunit mRNA levels in the pituitary, greater LH and FSH receptor mRNA in the testes, and greater testis size and 11KT levels.…”
Section: Alternative Male Phenotypessupporting
confidence: 91%
“…Several correlations have been found between the brain organization of fish and various ecological and behavioural patterns, such as diet and feeding habits (Huber et al 1997;Gonda et al 2009) and environmental and social factors (Lema et al 2005;Kihslinger et al 2006;Pollen et al 2007;Gonzalez-Voyer et al 2010;Kotrschal et al 2012;Lecchini et al 2014). Some of these factors might also explain the variability that we observed in the position of the OBs and the corresponding neuroanatomy of FMRFamide-ir NT components.…”
Section: Discussionmentioning
confidence: 66%
“…An indication of this comes from studying the brains and the behavioural repertoires of animals reared in captivity. Captive-bred animals generally have reduced behavioural diversity and less behavioural flexibility, and many regions of the brain are smaller and less active compared with wild counterparts [4][5][6][7]. Such reductions appear to be a by-product of the constant, non-demanding rearing environment [8,9].…”
Section: Introductionmentioning
confidence: 99%